1998
DOI: 10.1074/jbc.273.13.7185
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Alzheimer β-Fibrillogenesis by Melatonin

Abstract: It is generally postulated that the amyloid ␤ protein (A␤) plays a central role in the progressive neurodegeneration observed in Alzheimer's disease. Important pathologic properties of this protein, such as neurotoxicity and resistance to proteolytic degradation, depend on the ability of A␤ to form ␤-sheet structures or amyloid fibrils. We report that melatonin, a hormone recently found to protect neurons against A␤ toxicity, interacts with A␤1-40 and A␤1-42 and inhibits the progressive formation of ␤-sheets a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
239
2
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 318 publications
(249 citation statements)
references
References 54 publications
(41 reference statements)
6
239
2
2
Order By: Relevance
“…Tomiyama et al (1996) suggested that Rif binds to Aß by hydrophobic interactions between its lipophilic ansa chain and the hydrophobic region of Aß, thus blocking associations between Aß molecules leading to fAß formation. The anti-amyloidogenic and fibril-destabilizing activity of tetracycline (Tc), small-molecule anionic sulphonates or sulphates, melatonin, ß-sheet breaker peptides (iAß5) and nicotine may also be related to the propensity to bind to the specific sites of Aß (Kisilevsky et al 1995;Soto et al 1996;Pappolla et al 1998;Forloni et al 2001;Zeng et al 2001). Thus, it may be reasonable to consider that NSAIDs could exhibit their anti-amyloidogenic and fibril-destabilizing effects by directly binding to Aßs and/or fAßs.…”
Section: Discussionmentioning
confidence: 99%
“…Tomiyama et al (1996) suggested that Rif binds to Aß by hydrophobic interactions between its lipophilic ansa chain and the hydrophobic region of Aß, thus blocking associations between Aß molecules leading to fAß formation. The anti-amyloidogenic and fibril-destabilizing activity of tetracycline (Tc), small-molecule anionic sulphonates or sulphates, melatonin, ß-sheet breaker peptides (iAß5) and nicotine may also be related to the propensity to bind to the specific sites of Aß (Kisilevsky et al 1995;Soto et al 1996;Pappolla et al 1998;Forloni et al 2001;Zeng et al 2001). Thus, it may be reasonable to consider that NSAIDs could exhibit their anti-amyloidogenic and fibril-destabilizing effects by directly binding to Aßs and/or fAßs.…”
Section: Discussionmentioning
confidence: 99%
“…However, in recent experiments, the incubation of Ab in the presence of Cu 21 resulted in decreased Ab fibril formation, although no explanation for these processes at the atomistic level has been provided. [11][12][13] Although several theoretical and experimental studies have been conducted with the aim of explaining the interaction of Cu 21 and Ab, several contradictory results have emerged. 16 These contradictions might be explained by the different experimental conditions used by different research groups, which have included different pH values, 23 21 , Ab suffered conformational changes.…”
Section: Discussionmentioning
confidence: 99%
“…7 In addition, numerous compounds have been found to reduce Ab 1242 aggregation in vitro. 11,12 However, the usefulness of these compounds as inhibitors of Ab 1242 aggregation remains speculative due to their lack of specificity and/or unknown mechanism of action. For example, galanthamine (Reminil V R ; AChE inhibitor) has been recently demonstrated to interact with soluble Ab to inhibit the formation of the toxic oligomeric species in a concentration-dependent manner, but its mechanism of interaction has not been well established.…”
Section: Introductionmentioning
confidence: 99%
“…6 As Ab is toxic to neurons, 7 the main targets for therapeutic intervention of the Ab cascade include the inhibition of Ab production, the inhibition of Ab aggregation and fibril formation, in addition to the inhibition of the consequent inflammatory responses caused by the Ab deposition. In this context, several substances are known to inhibit Ab fibrillogenesis in vitro, including laminin, 6,8 melatonin, 9 nordihydroguaiaretic acid, 10 polyphenols, 11 site-directed monoclonal antibodies, 12 a1-antichymotrypsin, 13 Ginkgo biloba extract, 14 type IV collagen 15 and b-sheet breaker peptides. 16 Nevertheless, an effective therapeutic approach that interferes directly with the neurodegenerative process in AD is eagerly awaited.…”
Section: Introductionmentioning
confidence: 99%